2010
DOI: 10.1111/j.1468-1293.2009.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipid profile in highly active antiretroviral therapy‐naïve HIV‐infected patients in Cameroon: a case–control study

Abstract: Background HIV status has commonly been found to affect the serum lipid profile. Objectives The aim of this study was to determine the effect of HIV infection on lipid metabolism; such information may be used to improve the management of HIV‐infected patients. Methods Samples were collected from December 2005 to May 2006 at Yaounde University Teaching Hospital, Yaounde, Cameroon. Lipid parameters were obtained using colorimetric enzyme assays, while low‐density lipoprotein cholesterol (LDLC) values were calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
22
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 28 publications
12
22
2
3
Order By: Relevance
“…Our results were similar with other studies which documented significantly lower levels of TC, HDL-C and LDL-C cholesterol in treatment-naïve HIV-infected individuals relative to seronegative controls [21, 22]. Among all the lipid parameters in treatment-naïve HIV-infected patients, TG appeared to have an inconsistent report.…”
Section: Discussionsupporting
confidence: 90%
“…Our results were similar with other studies which documented significantly lower levels of TC, HDL-C and LDL-C cholesterol in treatment-naïve HIV-infected individuals relative to seronegative controls [21, 22]. Among all the lipid parameters in treatment-naïve HIV-infected patients, TG appeared to have an inconsistent report.…”
Section: Discussionsupporting
confidence: 90%
“…[17] Low TCH and HDL values as seen in this study have been reported in other earlier studies on lipid profile in HAART-naïve HIV patients. [141518] Our patients had low LDL levels similar to the findings of some other previous studies. [1819] However, some studies have reported high LDL in their patients.…”
Section: Discussionsupporting
confidence: 89%
“…Limitation of our study was that PIs were not used in any patient because our center provides only first-line ART according to NACO guidelines. In fact, untreated HIV infection is associated with low LDL and low HDL [31], particularly in those patients with severe immunesuppression [32]. It is therefore possible that high levels of LDL found in our study actually just reflect a "catch-up phenomenon".…”
Section: Discussionmentioning
confidence: 61%